Allelic Analysis of the Gli-B1 Locus in Hexaploid Wheat Using Reverse-Phase–Ultra-Performance Liquid Chromatography - Jong-Yeol Lee; Yu-Jeong Yang; Jinpyo So; Sewon Kim; Kyoungwon Cho (Molecules)
Wheat (Triticum aestivum L.) omega-5 gliadin, a major allergen responsible for wheat-dependent exercise-induced anaphylaxis in humans, is encoded by genes located at the Gli-B1 locus on chromosome 1B, which exhibits genetic polymorphism. Gli-B1 alleles have generally been identified based on the electrophoretic mobilities of the encoded gamma-, omega-1,2, and omega-5 gliadins in acid polyacrylamide gel electrophoresis. However, the similar mobilities of omega-5 gliadin variants make it difficult to distinguish them among different wheat varieties. In this study, we optimized reverse-phase–ultra-performance liquid chromatography (RP-UPLC) conditions to separate omega-5 gliadins in the reference wheat cultivar Chinese Spring and its nullisomic–tetrasomic lines for chromosome 1B. Five chromatographic peaks corresponded to omega-5 gliadin, and the average relative standard deviation to each peak retention time ranged from 0.31% to 0.93%, indicating that the method is accurate and reproducible for fractionating omega-5 gliadins in gliadin extracts from wheat flour. Using the optimized RP-UPLC method, we analyzed omega-5 gliadins in 24 wheat varieties with the Gli-B1f allele. The result showed that the wheat varieties were sorted into eight groups according to the composition of omega-5 gliadin, indicating that the classification of Gli-B1 alleles based on A-PAGE could not explain the composition of omega-5 gliadin in wheat. We reclassified 73 wheat varieties containing 16 unique Gli-B1 alleles into 31 groups based on the chromatographic patterns of their omega-5 gliadins. Our results provide information on the specific Gli-B1 alleles of wheat varieties belonging to each group and demonstrate the potential for RP-UPLC to facilitate genetic studies of wheat varieties.